Healthy lifestyle behaviors and hypertension among older adults in the United States (NHANES 2007-2010): Are there differences by race and ethnicity? - Philip M. DiMura MS; Margaret Gates Sc.D; Lenore Gensburg MS; Elizabeth Vasquez Dr.PH (Journal Of Aging Research And Healthcare, 2016)
Lifestyle modification has been shown to improve cardiovascular health. This cross-sectional study investigated the association of number of healthy lifestyle behaviors with hypertension across racial/ethnic categories using the National Health and Nutrition Examination Survey 2007-2010. The study population consisted of 4,363 individuals aged 40 years or older. Low risk lifestyle behaviors were assessed to obtain a health behavior score ranging from 0 to 5. Hypertension was defined based on average blood pressure measurements or current use of antihypertensive medication. The overall hypertension prevalence was 41%, with the highest prevalence in blacks (54%) and lowest in Mexican Americans (35%). Based on multivariable-adjusted logistic regression the odds of hypertension were significantly lower for whites with 3 (OR=0.56, 95% CI: 0.40, 0.77) and 4-5 (OR=0.53, 95% CI: 0.35, 0.80) healthy lifestyle behaviors, and for blacks who had 4-5 (OR=0.35, 95% CI: 0.18, 0.72) vs. 0-1 healthy lifestyle behaviors. There was no statistically significant association between number of healthy lifestyle behaviors and odds of hypertension in Mexican Americans. These results suggest that healthy lifestyle behaviors are associated with lower prevalence of hypertension in whites and blacks, but additional research is needed to identify protective factors for Mexican Americans.
Keywords: hypertension